MODULATION IN INDONESIAN TRANSLATION OF NATIONAL GEOGRAPHIC ARTICLES - Setiawan, Hanif Pandu; Yuliasri, Issy (ELT Forum: Journal of English Language Teaching, 2018)
This study investigates the types of modulation which were used on the translationprocess of National Geographic Magazine of June 2014 both on USA andIndonesian issue. The purposes of this study areto describe the use of modulation intranslating â€œNational Geographicâ€ from English to Indonesian and to describe themaintenance of the source target meaning in the target text. The qualitativeapproach was used to describe the quantitative data which was got from theanalysis. The data of this study was collected using reading and inventorying stagesand analyzed using comparing, identifying, and evaluating process. The collecteddata then was analyzed to investigate the modulationâ€Ÿs impact on messagemaintenance. Based on those analyses, substitution has the highest rank ofmodulation type used on the magazineâ€Ÿs articles (37.8% of total 111 data) followedby reversal (34.2%), deviation (14.4%), specification (8.1%), and generalization(5.4%) sequentially. This result is linear to the maintenance of message rating whichwas taken from five English Department lecturer raters. It shows that the highestnumber of score 3 (well delivered) percentage ratio is obtained by specification(75.5%) followed by reversal (72.6%), deviation (72.5%), substitution (71.2%) andgeneralization (60%). From the result above it can be seen that the more frequentoccurrence does not always mean to be so effective compared to the less frequentone. The highest percentage of successful maintenance was obtained byspecification, which is on 4th rank on the frequency of occurrence table. The mostfrequent type of modulation, substitution, only settles on 4th rank on the table ofscore 3. On the other hand, the most distorted type of modulation is gotten byreversal with 9.5% on score 1, while the least distorted one is gotten bygeneralization.